STATE POLICY TOOLS FOR ACTIVATION OF THE DIGITALIZATION PROCESSES OF THE TOURIST COMPLEX OF UKRAINE - VASYLTSIV, Taras; NAKONECHNA, Nataliya (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article focuses on issues of formation and implementation of the state development policy and effective use of the tourism potential of the country and its regions. Emphasis is placed on the perspective of an integrated approach and development of the tourism complex of the region, consisting of a number of economic entities both directly and adjacent to tourism. It is shown that one of the modern trends, which determines the majority of processes in both tourism and the economy, is the digital transformation of the economy and society.Based on these principles, the purpose of the research is to justify the instruments of the state policy of activating the processes of digitization of the tourist complex of Ukraine. The directions and instruments of the state policy of stimulating the processes of digital development in the tourist complex of the region have been determined. In particular, it is about (1) digitalization of business processes of business entities that form a tourist complex, (2) development of a digital communication system both in the system of entities of the complex and with consumers of services, (3) effective use of Internet tools marketing at different levels of management.It was established that quick and deep consequences of the transition of the tourist complex to "digital" will be possible only when "digital" transformation will become the basis of the life of all subjects of this sector of the economy, business and state institutions, will be a common and everyday phenomenon, will be a key agenda on the way to prosperity and the basis of well-being. In the era of the digital economy, the main resource is inexhaustible, accurate, reliable, truthful and timely information. The main platform for the development of the digital economy is the virtual network of the unlimited Internet.
Keywords: tourism; tourist complex; state regulation; development; region; digitization; state policy; tools; means